Perancangan Sistem Pengisian Accumulator Mobil Listrik dengan Sumber Listrik Solar Cell Berbasis Mikrokontroler - Hafelzan Enang Edovidata; Aswardi Aswardi (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Technological developments in the automotive field have led to an increase in the use of fuel which will eventually run out and have a negative impact on the environment. Overcoming this problem was developed an electric car that uses electricity as its energy source and is also environmentally friendly because it does not have exhaust emissions. One source of electrical energy is the utilization of solar energy using solar panels that can convert sunlight energy into electrical energy, this technology is called solar cells. The electrical energy from this solar cell must be connected to the storage media, which is the battery (accumulator). In this study the electrical energy storage system to the battery uses an arduino controlled buck converter circuit with the Pulse Width Modulation (PWM) method to reduce and stabilize the voltage by 14.4 Volts so that it does not cross the battery charging threshold of 14.4 -15 VDC to maintain The battery does not damage quickly.